Analisis Peristiwa Tutur Dalam Komunikasi Lintas Budaya Gorontalo-Jawa Di Desa Banuroja (Teori Speaking Dell Hymes) - Walangadi, Sandi; Hinta, Ellyana; Umam Kau, Munkizul; Sartika, Eka (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to describe the speech events occurring in cross-cultural communication between Gorontalo and Javanese communities in Banuroja village. The method used was descriptive. The data and sources examined were conversations among the residents of Banuroja village. Data collection techniques included observation, interviews, and documentation. Data analysis techniques encompassed data reduction, data display, and conclusion. The result and discussion of the study are as follows: (1) Setting and scene: in the morning and at residents’ homes. (2) Participants: two to four people. (3) Ends: obtaining information about common activities conducted by the community. (4) Act sequences: forms of speech include declarative and interrogative sentences in a relaxed language variety. (5) Key: the tone of speech comprises three types: soft from Javanese speakers, firm and high from Gorontalo language channel appears, featuring Gorontalo-Javanese registers and dialects. The communication between Gorontalo and Javanese communities in Banuroja village fosters mutual understanding, as speakers share common concerns, which become the focus of conversation, referred to as Ends in Hymes’ terminology.